Kyoto : - Gouverneur, Mosher (C.E. Tuttle Co., 1964)
The book falls into three parts are a narrative which devotes a chapter to each location and discusses its background, its place in history, and its noteworthy aspects, offering insights into its essence and bringing it alive for the reader. Taken as a whole, th narrative tells the story of Kyoto, and a comprehensive guide to each of the sixteen sights, plus associated establishments, and then getting there and back provides complete information on the practical aspects of visiting each place, including public transportation routes.